Extrafiscalidade tribut??ria enquanto instrumento de mitiga????o dos efeitos da crise financeira internacional p??s-2008: uma an??lise da efic??cia das medidas antic??clicas de desonera????o - Santana, Pricilla Maria (2016)
The international financial crisis of 2007/2008 unleashed several events that combined lead to one of the worst crises of capitalism. As a reaction, the governments engaged in many efforts to mitigate its effects. The search for countercyclical measures became the center of the economic policy. In Brazil, the adoption of an active fiscal policy based on a package of tax reflief applied to specific sectors was one of the principle measures. In a clear rescue of the extrafiscal dimension of the Tax on Manufactured Products (IPI), it was implemented a systematic reduction of aliquots for durable white goods and furniture. This dissertation aims at evaluating the efficacy of these measures as well as to demonstrate and recognize the relevant strategic role of tax measures in the incentive or disincentive of specific behaviors. Therefore, an econometric model was developed, where from a set of regressions, it sought to verify if the measures of fiscal (tax reflief), credit and monetary policy, directed to the automotive, furnishings, domestic appliance, and construction materials sectors, were effective on boosting the economy, meantime keeping the levels of consumption and sectional production. The results point to an effectiveness of the monetary policy to the automotive and domestic appliance sectors, whereas the credit policy was efficacious in the sectors of civil construction, furnishings and domestic appliance. By its turn, the fiscal policy was effective and was able to leveraging the automobile sales. To the other sectors, the fiscal policy results were not satisfactory. Although the empiric results founded point to a moderate use of the fiscal policy, this study demonstrated in an unequivocal way the role of extrafiscal taxes, notably on IPI. Finally, it is noteworthy to mention that, as all econometric model, this one also has its limitations, in special, those related to the data availability, making necessary the use of proxies.